Digital Literacy and Perception of UCIC Business Management Students Supporting Cloud Accounting - Kartika, Ika; Gitama, Gytha Nurhana Dhea Praadha; Dewi, Dessy Kumala; Parlina, Nurhana Dhea (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study investigates the influence of students’ digital perception and digital literacy on the sustainability of cloud accounting usage. Using a quantitative approach, data were collected through questionnaires distributed to 50 students. Validity and reliability tests were conducted to ensure the instrument's quality. All statement items were valid, and the reliability scores for all variables indicating high reliability. Multiple linear regression was used to analyze the data. The t-test showed that digital perception had no significant effect on cloud accounting usage, while digital literacy had a significant effect. The F-test revealed that both variables together significantly influenced cloud accounting usage. The coefficient of determination indicating that 76.4% of the variance in cloud accounting usage was explained by digital perception and digital literacy. These results emphasize the vital role of digital literacy in promoting sustainable cloud accounting practices among students in the digital era. Keywords: Digital Perception; Digital Literacy; Cloud Accounting, Sustainability; Students